VR-supported English language learning: Applications, benefits, and challenges - Ulzhan Urazаliyeva; Gulzhaina K. Kassymova; N. Salem; D. Hariyanto; Mohamed Nor Azhari Azman; Ardak Kenesbayevna Kalimoldayeva; Svetlana Amanzholovna Urazgaliyeva; Yerassyl Kuatuly Talgatov (LPMPP Universitas Negeri Yogyakarta, 2026)
This article focuses on theoretical foundations of virtual reality-supported language learning and theoretically proves that Virtual Reality (VR) has emerged as a promising technology for enhancing English language learning by providing immersive, interactive, and context-rich learning experiences. However, existing research remains fragmented across different language skills, educational contexts, and technological applications. This study aims to systematically synthesize empirical evidence on the use of VR in English language learning and examine its reported benefits, underlying learning mechanisms, implementation challenges, and future research directions. A systematic narrative review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Literature searches was performed in Scopus, Web of Science, ERIC, and Google Scholar, supplemented by manual searches of relevant references. A total of 160 records were identified, of which 10 empirical studies met the inclusion criteria and were included in the qualitative synthesis. The findings indicate that VR has been applied to support vocabulary acquisition, speaking, listening, writing, pronunciation, and intercultural communication. Across the reviewed studies, VR was associated with increased learner engagement, improved vocabulary retention, enhanced communicative competence, reduced language anxiety, and greater learning motivation. The review further suggests that these outcomes may be explained by the mechanisms of immersion, presence, embodiment, situated learning, and flow theories. Despite these benefits, challenges related to cost, technical infrastructure, accessibility, teacher preparedness, and ethical considerations continue to affect implementation. The review identifies several research gaps, including the need for longitudinal studies, larger participant samples, stronger representation of teacher perspectives, and more inclusive VR design. Thus, literature review suggests that VR represents a valuable complementary tool for English language education when integrated through sound pedagogical practices and adequate institutional support.